Clinical and Demographic Characteristics of Upper Limb Dystonia. Issue 11 (26th August 2020) - Norris, Scott A.; Jinnah, Hyder A.; Klein, Christine; Jankovic, Joseph; Berman, Brian D.; Roze, Emmanuel; Mahajan, Abhimanyu; Espay, Alberto J.; Murthy, Avinash V.; Fung, Victor S.C.; LeDoux, Mark S.; Chang, Florence C.F.; et al.
ABSTRACT: Background: Knowledge of characteristics in upper limb dystonia remains limited, derived primarily from small, single‐site studies. Objective: The objective of this study was to characterize demographic and clinical characteristics of upper limb dystonia from the Dystonia Coalition data set, a large, international, multicenter resource. Methods: We evaluated clinical and demographic characteristics of 367 participants with upper limb dystonia from onset, comparing across subcategories of focal (with and without dystonia spread) versus nonfocal onset. Results: Focal onset occurred in 80%; 67% remained focal without spread. Task specificity was most frequent in this subgroup, most often writer's cramp and affecting the dominant limb (83%). Focal onset with spread was more frequent in young onset (<21 years). Focal onset occurred equally in women and men; nonfocal onset affected women disproportionately. Conclusions: Upper limb dystonia distribution, focality, and task specificity relate to onset age and likelihood of regional spread. Observations may inform clinical counseling and design, execution, and interpretation of future studies. © 2020 International Parkinson and Movement Disorder Society